Radicalism in the South since Reconstruction
VIII, 274 p. 1 illus.
Keywords: This book broadly frames the scholarly conversation about southern radicalism, putting essays covering a range of historical periods and topics in dialogue with each other so as to get a sense of the range of southern politics and history.